Uma jornada para além do esperado: o épico de Gilgamesh e suas verossimilhanças na narrativa épica de Homero - SANTOS JÚNIOR, Edimar Ribeiro dos (2021)
The present research aims to debate and analyze one of the oldest literatures produced by mankind known as the Gilgamesh epic, having as its main objective the perception of the dissemination of this literary work within the Mesopotamian territorial space, but mainly the scope of its influence even in the West, specifically in the Greek world. For these purposes we sought to explore the Ninivite version of the Gilgamesh epic, known as the “standard” version by pointing out specific points that are similar in another important epic literature of Antiquity Homero‟s Odyssey. By incorporating P. Burkef‟s reflections on culture and cultural hybridism,as well as W. Burkert and M. West, C. Penglase and E. Said‟s approaches within an Orientalist view. Far from wishing to provide a definitive answer around such a vast, deep and gaping topic, this article aims to draw a debate about the development and diffusion of this epic in ancient Mesopotamia as a way of observing the influences of this rich culture on the ancient world.